The Impacts of Tourism Risk Management, IT Adoption, Agility and Resilience on the Sustainable Tourism Supply Chain Performance of Maldives’ Tourism Industry - Muhammad Azhar Bhatti; Muhammad Atif Nawaz (iRASD Journal of Management)
Recently, the tourism industry has a significant role in economic growth worldwide and attain the attention of recent researchers. Therefore, the ongoing study aims to examine the role of tourism IT adoption, TR management orientation, and tourism agility on the sustainable tourism supply chain performance (STSCP) of Maldives’ tourism industry. The investigation of mediating role of tourism supply chain resilience among the nexus of tourism IT adoption, TR management orientation, tourism agility, and sustainable tourism supply chain performance of Maldives’ tourism industry are also included in the goal of the ongoing study. The data were obtained using questionnaires from the tourism industry employees related to the supply chain process, and AMOS has been utilized for analysis purposes. The results indicated that tourism IT adoption, TR management orientation, and tourism agility positively associate with the sustainable tourism supply chain performance of the Maldives’ tourism industry. The findings also exposed that tourism supply chain resilience has played a positive mediating role among the nexus of tourism IT adoption, TR management orientation, tourism agility, and STSCP of the Maldives’ tourism industry. These findings are guided to the policy developers and implementers that they should increase their focus on the tourism industry that could enhance the country's economic growth.